Gyula Farkas Budapest Gypsy Band, Side A
live recording of the concert in Paris in 1997, Blitz csardas; Brahms, 5th Hungarian Dance; Erkel, Palotasche, Offenbach, Orpheus in the Underworld; Ede Reményi, Fly, my swallow; Strauss, Tritch-tratch polka